A colorimetric and fluorescent chemosensor for Hg2+ based on a photochromic diarylethene with a quinoline unit. Issue 70 (28th November 2018) - Guo, Shuli; Fan, Congbin; Liu, Gang; Pu, Shouzhi
Abstract : A new colorimetric and fluorescent 'on–off' chemosensor, 1O, based on a photochromic diarylethene with a quinoline unit was designed and synthesized. Abstract : A new colorimetric and fluorescent 'on–off' chemosensor, 1O, based on a photochromic diarylethene with a quinoline unit was designed and synthesized. The chemosensor1O demonstrated selective and sensitive detection of Hg 2+ ions in the presence of other competitive metal ions in acetonitrile. The stoichiometric ratio of the sensor1O for Hg 2+ was determined to be 1 : 1, and the limit of detection of the probe1O was calculated to be 56.3 nM for Hg 2+ . In addition, a molecular logic circuit with four inputs and one output was successfully constructed with UV/vis light and metal-responsive behavior. ESI-MS spectroscopy, Job's plot analysis, and 1 H NMR titration experiments confirm the binding behavior between1O and Hg 2+ .